Possibility of an independent Catalonia: the scope of the principle of self-determination under public international law - Gūtmane, Līga (Riga Graduate School of Law, 2018)
The paper aims to examine the scope and applicability of the right to self-determination and its relationship with the principle of territorial integrity to conclude as to whether there exists a right to unilateral non-colonial secession and in what circumstances it can be exercised. Moreover, an absence of the explicit right to unilateral secession does not preclude the act itself, therefore, the paper will also examine the question of statehood and the issue of recognition, particularly important in the case of Catalonia. Lastly, the paper aims to scrutinize the case of Catalonia on the basis of the relevant criteria that needs to be present in order to claim the right to unilateral non-colonial secession as well as the conditions on which a political entity constitutes a state.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Public international law; Self-determination; Catalonia